Greek Far-Right: the Formation of an Autonomous Political Space in the 21st Century (Balkan Politics: Political Parties in the Balkans, 1991-2024, 2025)
The 1990s marked Greek politics and society with a series of events. In the po-litical field, at the beginning of the decade, significant political conflicts erup-ted, linked to a major financial scandal in which the then Prime Minister and key government officials were allegedly involved. At the same time, internatio-nal events following the collapse of the Eastern Bloc and the subsequent chan-ges (e.g., in migration flows) directly affected political parties and the political system. This instability had immediate consequences for Greek political parties as well as society. As in other European countries, in Greece too, significant levels of dissatisfaction and political cynicism also begin to emerge, while abstention rates start to concern the entire political establishment. Thus, this marked the beginning of a continuous period characterized by both a crisis of represen-tation and a legitimacy crisis, which, with various fluctuations, spans at least a two-decade-long course. Among the multiple crises that arise, new political parties emerge that differentiate themselves from the mainstream parties, with rhetoric focusing partly or entirely on critiquing the democratic model and the practices of Metapolitefsi2, and gradually affecting the entire political landscape. A key player in this effort is Laikos Orthodoxos Synagermos (LA-OS-Popular Orthodox Rally), a radical far-right party that appears in the early 2000s and will play a decisive role in renewing conservatism and reshaping the party system.